اليات حماية الطفل المحضون في التشريع الجزائري - حيياوي فتيحة (المسيلة, 2023)
هدف هذا البحث إلى التعرف على الآليات التي وضعها المشرع الجزائري لحماية الطفل المحضون، والمتمثلة في: الحق في الحضانة، الحق في الزيارة، الحق في مشتملات النفقة وذلك حرصا على مصلحة المحضون المادية والمعنوية. كما هدف كذلك ( البحث) إلى التعرف على الآليات الجزائية التي أقرها القانون وذلك بتجريم الأفعال الواقعة على الطفل المحضون وهي: جرائم الامتناع عن تسليم الطفل لحاضنه، والامتناع عن تنفيذ حكم الزيارة، جريمة إختطاف قاصر وجريمة إبعاد المحضون، وكذا جريمة الامتناع عن تسديد النفقة. وتطرقنا أيضا في هذا البحث إلى دور القضاء الاستعجالي في حماية الحقوق المتعلقة بالمحضون من خلال إصدار أوامر استعجالية لحماية المحضون، قبل الفصل في الموضوع، قد أدرجها في المادة 57 مكرر من قانون الأسرة الجزائري كما يلي: حق الحضانة المؤقتة، حق الزيارة المؤقتة، حق السكن المؤقت، حق النفقة المؤقتة. Abstract: The aim of thisresearchis to identify the mechanisms put in place by the Algerian legislator to protect the fosteredchild,represented in: the right to custody, the right to visitation, the right to the contents of alimony, in the interest of the material and moral interest of the fosteredchild. The researchalsoaimed to identify the penalmechanismsapproved by the law by criminalizing the actscommittedagainst the fosteredchild, whichare: the crimes of refrainingfromhanding over the child to hiscustodian, and refrainingfromimplementing the visitation ruling, the crime of kidnapping a minor and the crime of deporting the fosteredchild, as well as the crime of refrainingfrompayingalimony. In thisresearch, wealsotouched on the role of the urgent judiciary in protecting the rightsrelated to the fosteredchild by issuing urgent orders to protect the fosteredchild, beforedeciding on the matter, whichheincluded In Article 57 bis of the Algerian Family Code : the right of temporarycustody, the right of temporary visitation, the right of temporaryhousing The right to temporaryalimony.
Keywords: اليات الحماية - الطفل المحضون - التشريع الجزائري